Productivity and competitiveness determination of the small-scale mining at the northern mining district in the state of Boyacá (2013)
In recent years, mining in Colombia has been growing to such an extent that the country is considered to be the largest producer of coal in Latin America and the 12th in the world. In the Department of Boyacá, specifically, the coal mining production generated an economic movement closed to 380 000 million pesos last year the need to know the level of productivity and competitiveness of small-scale mining in the mining district of the north of this department, promotes this investigation. This documentation contains a study of twenty mining titles located in different municipalities of this mining district, which allowed us to identify the strengths and weaknesses in areas of productivity and competitiveness of small-scale mining of the district. Likewise, it raises a number of mechanisms and strategies to improve, from the business standpoint, he shortcomings presented by the small-scale mining sector.